Upregulation of matrix metalloproteinase-9 in the cerebrospinal fluid of patients with acute Lyme neuroborreliosis. Issue 3 (1st March 2000) - Kirchner, Annette; Koedel, Uwe; Fingerle, Volker; Paul, Robert; Wilske, Bettina; Pfister, Hans-Walter
Abstract : It was investigated (1) whether metalloproteinase-9 (MMP-9), MMP-3, and tissue inhibitor of matrix metalloproteinase-1 (TIMP-1, the natural tissue inhibitor of MMP-9) are increased in the CSF of patients with Lyme neuroborreliosis and (2) whether macrophages can express MMP-9 when stimulated with Borrelia burgdorferi . Zymography showed MMP-9 activity in 26 of 31 (84%) CSF samples from patients with acute stage 2 Lyme neuroborreliosis, but not in 20 controls with non-inflammatory neurological disorders. Activity of MMP-2 was detected in all CSF samples in both patients with neuroborreliosis and controls, suggesting a constitutive release of MMP-2. Using enzyme linked immunosorbent assay (ELISA) MMP-3 (which can activate MMP-9) was detected in low concentrations in the CSF of 13 of 29 patients with neuroborreliosis, but not in controls. TIMP-1 was increased twofold in CSF samples from patients with neuroborreliosis in comparison with the controls. MMP-9 activity was induced in vitro in a mouse macrophage cell line (RAW 264.7) when stimulated with two different genospecies of B burgdorferi ( B garinii, B afzelii ). This MMP-9 activity was reduced in a dose dependent manner when macrophages stimulated with B burgdorferi were coincubated with NF-κB SN50, a cell permeable peptide which inhibits the translocation of NF-κB into the nucleus of stimulated cells. The data show that (1) MMP-9 activity is present in the CSF of patients with neuroborreliosis, (2) macrophages stimulated with B burgdorferi are a possible source of MMP-9 increase, and (3) activation of NF-κB may play a part in the upregulation of MMP-9 by B burgdorferi .